A Corpus Stylistic Analysis of The Tell-Tale Heart by Edgar Allan Poe - Wasif Hussain (Journal of Applied Linguistics, 2025)
This paper explores how Edgar Allan Poe's "The Tell-Tale Heart" creates an atmosphere of psychological tension and guilt through language. Using linguistic analysis tools, the study investigated how the text's language reflected the narrator's psychological state, contributing to themes of tension and madness. Two key questions guide the analysis: how Poe's language establishes tension and guilt and how his linguistic choices portray the narrator's descent into madness. By examining word patterns, relationships between words, and word usage frequencies, the study highlights how specific language features contributed to the story's psychological and thematic depth. This research demonstrated the value of linguistic analysis in understanding both the poetics and psychological aspects of literary texts. Keywords : Corpus Stylistics; Gothic Literature; detective story, Psychological Tension; Madness